Development of novel, chemically-modified hempseed protein adhesives for wood bonding applications - Barretto, Roselle Paulasa (My University, 2025)
The dominance of petroleum-derived and formaldehyde-based wood adhesives poses serious environmental and health challenges, emphasizing the urgent need for sustainable, fully bio-based alternatives. This dissertation investigates the development of hempseed protein adhesives through a comprehensive approach involving extraction, structural characterization, and systematic chemical modification aimed at improving bonding performance, thermal stability, and water resistance. Hempseed protein, rich in edestin (11S) and albumin (7S) fractions, represents a renewable and abundant biopolymer with intrinsic adhesive potential. In the first study, hempseed protein isolates (HPI) were successfully extracted from commercial and Hlesia hempseed meals using alkaline solubilization and isoelectric precipitation. Structural analyses identified major protein subunits with molecular weights of 18–20 and 34 kDa, corresponding to edestin and albumin fractions. The native HPIs showed promising adhesive properties attributed to their intrinsic high hydrophobic amino acid content, which confers low water solubility and contributes to inherent wet bonding strength. Crosslinking with glutaraldehyde at optimal concentrations (20–80 [mu]M) significantly enhanced adhesive performance, with dry shear strengths up to 5.74 MPa and wet strengths up to 2.86 MPa at press temperatures of 190 °C. Notably, crosslinked HPIs maintained substantial wet adhesion at lower press temperatures (150–170 °C), broadening processing windows. Morphological characterization via SEM revealed smoother, more compact fracture surfaces in modified adhesives, indicative of improved cohesive bonding and interfacial adhesion. The second study evaluated bio-based modifications employing glyoxal and zinc chloride (ZnCl₂) as crosslinkers. Glyoxal modification markedly increased adhesive strength across all conditions, achieving dry, wet, and soaked shear strengths of up to 5.69, 2.68, and 4.91 MPa, respectively. ZnCl₂ induced moderate but consistent improvements, with corresponding strengths of 4.20, 2.10, and 3.89 MPa. Combining glyoxal and ZnCl₂ yielded intermediate performance, suggesting limited synergistic interaction. Thermal analysis demonstrated substantial enhancement of thermal stability upon glyoxal treatment, with denaturation temperatures elevated to approximately 146–148 °C and corresponding increase in enthalpy, indicating strengthened protein network structures. SEM images corroborated densification of the adhesive matrix with glyoxal, contrasted with less compact morphology for ZnCl₂ modifications. Surface hydrophobicity increased significantly with glyoxal, supporting improved moisture barrier properties essential for wet-performance. Rheological assessments revealed stable shear-thinning behavior suitable for processing, with pot-life viscosity stability maintained for up to 24 hours at 25 °C and under refrigerated conditions, ensuring feasibility for industrial application. The third study focused on fully bio-based adhesive formulations through synergistic crosslinking of HPIs with glucose and citric acid, leveraging Maillard-type and esterification chemistry. Citric acid modification alone enhanced crosslink density, raising a dry shear strength to 3.07 MPa and thermal stability above 144 °C denaturation temperature. Glucose contributed to formation of Schiff bases and Maillard reaction products, leading to further gains in dry strength (maximum 3.46 MPa) and wet strength (1.61 MPa) as well as increasing surface hydrophobicity over to 78 [mu]g/mg protein. When combined, glucose and citric acid yielded strong synergistic effects, with adhesive strengths reaching 4.76 MPa (dry), 2.49 MPa (wet), and 4.14 MPa (soaked), alongside durable water resistance demonstrated by retention of 82.9% mass after soaking. DSC analysis indicated cooperative stabilization reflected in increased denaturation and endset temperatures exceeding 160 °C and elevated enthalpy values. FTIR and XRD analyses confirmed formation of ester bonds and dense amorphous networks concomitant with reduction of salt crystallinity. SEM revealed continuous, crack-free fracture textures consistent with robust interfacial bonding and cohesive strength. Rheological properties showed balanced viscoelastic behavior, ensuring processability and application stability. Collectively, these studies establish the mechanistic basis and processing strategies for converting hempseed proteins into high-performance, formaldehyde-free wood adhesives. The results not only demonstrate the feasibility of hempseed protein as a competitive biopolymer but also advance the broader adoption of sustainable adhesive technologies within the bioeconomy.
Keywords: Biobased adhesive; Hempseed; Hempseed protein; Chemical crosslinking; Plant protein; Protein adhesive